Fiction and Theories of Personal Maturity - Qurbonov Asqar Bahodir o‘g‘li; Xudoyqulov Surojiddin (Researchparks Publishing, 2022)
Institutions of higher and secondary special social and economic education are designed for students majoring in socio-economics and spirituality, with the acquisition of theoretical knowledge as well as practical knowledge. Strengthening skills, literary, pedagogical, socio-economic, spiritual foundations, the human factor, areas of domestic work, material and spiritual living conditions of people, the role of fiction in the spiritual development of the individual, philosophical analysis, human education, its laws The study of pedagogy determines the transfer of ideas, ideas, interest in fiction in the integration of knowledge and skills, the initial knowledge, skills and abilities of our country in the world. The unparalleled role of modern socio-economic, material and spiritual, advanced technologies today, the passion for work, the conscious choice of profession, the imagination of mental and physical labor for the benefit of society and the individual, and is a thought-provoking educational article. The radical changes in the students, the renewal of the pages, the results of the reforms are aimed at raising the living standards of our people to the level of highly developed democracies. Improving the education system, deepening the ability of young talented students, instilling in them the secrets of the pursuit of knowledge, love of work, respect for the working man and further prepare him for useful work. As a result of the active participation of students in social work, they are brought up in such noble moral qualities as social attitude to work, care and preservation of public property, respect and love for the working people. Activity, initiative, orderliness, organization, discipline and responsibility, as well as cultivating a sense of mutual support are among the main tasks of today.